Network intrusion detection in internet service provider (ISP) / Aini Ahmad - Ahmad, Aini (2017)
DDos - is a volumetric attack that comes from multiple sources toward a targeted object (website and servers) which its intention either to make targeted object unavailable for legitimate user.